A Cooperative Intelligent Transport Systems (C‐ITS)‐based lane‐changing advisory for weaving sections. Issue 5 (4th April 2016) - Mai, Trung; Jiang, Rui; Chung, Edward
Summary: Weaving sections, a common design of motorways, require extensive lane‐change manoeuvres. Numerous studies have found that drivers tend to make their lane changes as soon as they enter the weaving section, as the traffic volume increases. Congestion builds up as a result of this high lane‐changing concentration. Importantly, such congestion also limits the use of existing infrastructure, the weaving section downstream. This behaviour thus affects both safety and operational aspects. The potential tool for managing motorways effectively and efficiently is cooperative intelligent transport systems (C‐ITS). This research investigates a lane‐change distribution advisory application based on C‐ITS for weaving vehicles in weaving sections. The objective of this research is to alleviate the lane‐changing concentration problem by coordinating weaving vehicles to ensure that such lane‐changing activities are evenly distributed over the existing weaving length. This is achieved by sending individual messages to drivers based on their location to advise them when to start their lane change. The research applied a microscopic simulation inaimsun to evaluate the proposed strategy's effectiveness in a one‐sided ramp weave. The proposed strategy was evaluated using different weaving advisory proportions, traffic demands and penetration rates. The evaluation revealed that the proposed lane‐changing advisory has the potential to significantly improve delay. Copyright © 2016 John Wiley & Sons, Ltd.